Self-management behavior and its influencing factors among adults with chronic obstructive pulmonary disease in Colombo, Sri Lanka: A cross-sectional study - Kanchana Warnakula Royal Weerasooriya; Niphawan Samartkit; Khemaradee Masingboon; Pachanok Witheethamasak (Belitung Nursing Journal)
Background: Self-management behaviors are essential to take care of chronic obstructive pulmonary disease (COPD). However, data on COPD self-management practices in Sri Lankan adults is limited. Therefore, identifying the level of COPD self-management and examining its influencing factors are essential for healthcare providers to manage COPD effectively.